Morphology and multigene phylogeny reveal a new species and a new record of Rhytidhysteron (Dothideomycetes, Ascomycota) from China - De Silva, N. I; Tennakoon, D. S; Thambugala, K. M; Karunarathna, S. C; Lumyong, S; Hyde, K. D. (Asian Journal of Mycology, 2020)
Rhytidhysteron is an ecologically diverse group of Dothideomycetes occurring as endophytes, saprobes and weak pathogens on woody plants in terrestrial and intertidal habitats. During our field surveys in China, we collected Rhytidhysteron species on dead twigs of Magnolia grandiflora and decaying wood of Morus australis. Both morphology and multigene phylogenetic analyses showed one taxon to be a new species, while the other is a new record of Rhytidhysteron thailandicum. Combined LSU, SSU, ITS and tef1 sequence data were used for the phylogenetic analyses. Descriptions, micrographs and a phylogenetic tree to show the placement of the two species in Rhytidhysteron (Hysteriaceae) are provided.
Keywords: 1 new taxon – Hysteriaceae – Hysteriales – Magnolia grandiflora – Morus australis – Rhytidhysteron magnoliae